Aberrant Functional Connectivity of the Posterior Cingulate Cortex in Type 2 Diabetes Without Cognitive Impairment and Microvascular Complications - Cheng, Panpan; Song, Shuyan; Li, Yumin; Zhang, Yao; Yi, Jun; Xu, Xiangyang; Zhou, Hongmei; Zuo, Zhentao (Frontiers in Endocrinology, 2021)
Objective: To investigate the alterations of brain functional connectivity (FC) in type 2 diabetes mellitus (T2DM) patients without clinical evidence of cognitive impairment and microvascular complications (woCIMC-T2DM) using resting-state fMRI (rs-fMRI), and to determine whether its’ value was correlated with clinical indicators. Methods: A total of 27 T2DM and 26 healthy controls (HC) were prospectively examined. Cognitive impairment was excluded by MMSE and MoCA scales, and microvascular complications were excluded by fundus photography, microalbuminuria, and other indicators. The correlation maps, derived from rs-fMRI with posterior cingulum cortex (PCC) as the seed, were compared between T2DM and HC. Pearson correlation analysis was performed to determine the relationships between the FC of PCC and clinical indicators. Results: Compared with HC, woCIMC-T2DM patients showed significantly decreased FCs with PCC (PCC-FCs) in the anterior cingulate cortex (ACC); right superior frontal gyrus; right medial frontal gyrus, and right angular gyrus. Meanwhile, increased PCC-FCs was observed in the right superior temporal gyrus, calcarine fissure (CAL). The FC of PCC-ACC was negatively correlated with HbA1c and diabetes duration, and the FC of PCC-CAL was significant positive correlated with HbA1c and diabetes duration. Conclusion: The functional connectivity, especially between PCC with cognitive and visual brain regions, was altered before clinically measurable cognitive impairment and microvascular complications occurred in T2DM patients. In addition, the functional connectivity between PCC with cognitive and visual brain regions were correlated with HbA1c and diabetes duration. This indicates that clinicians should not only pay attention to blood glucose control, but also to brain function changes before the occurrence of adverse complications, which is of great significance for the prevention of cognitive dysfunction and visual impairment.